PENINGKATAN HASIL BELAJAR SISWA MELALUI PENERAPAN METODE DISKUSI PARTISIPATIF PADA SISWAKELAS IV SD NEGERI BUNG KECAMATAN TAMALANREA KOTA MAKASSAR - Musbaing Musbaing (ALGAZALI INTERNATIONAL JOURNAL EDUCATIONAL RESEARCH, 2020)
ABSTRACT: Improving Student Learning Outcomes through the Method of Participatory Discussion On the Students Class IV of SD Negeri Bung District Tamalanrea Makassar City. Day is aim at the goal to determine the effectiveness of the use of Methods of Participatory Discussion in improving student learning outcomes. The type of this research is using classroom action research. The subject of this study as many as 35 students of class IV SD Negeri Dude Makassar, this Study is divided into 2 cycles. This study lasted for one month which consists of 4 meetings, data Collection was done qualitatively that obtained from the observation during the teaching and learning process during the study and the quantitative are obtained from the test results of the learning of subjects in each cycle. Furthermore, the data were analyzed qualitatively, which describes the results of actions during the learning process, and quantitatively by using descriptive statistics, namely the average score, frequency table, minimum value, maximum value and distribution tables and percentages. The results of this study showed that the activeness of students in the learning process and learning outcomes of students has increased through the application of the Method Participatory Discussion. It is based on the data obtained from the studies conducted in Cycle I with the learning outcomes of students 63,42% and sikulus cycle II with the results of the student learning 76%.Keywords : Hasill learning, Participatory Discussion.